Nutritional status in post SARS-Cov2 rehabilitation patients. Issue 12 (December 2022) - Gobbi, M.; Brunani, A.; Arreghini, M.; Baccalaro, G.; Dellepiane, D.; La Vela, V.; Lucchetti, E.; Barbaglia, M.; Cova, A.; Fornara, E.; Galli, S.; Cimolin, V.; et al.
Summary: Background & aims: After prolonged hospitalization, the assessment of nutritional status and the identification of adequate nutritional support is of paramount importance. In this observational study, we aimed at assessing the presence of a malnutrition condition in SARS-Cov2 patients after the acute phase and the effects of a multidisciplinary rehabilitation program on nutritional and functional status. Methods: We recruited 48 patients (26 males/22 females) admitted to our Rehabilitation Unit after discharge from acute Covid Hospitals in northern Italy with negative swab for SARS-Cov2. We used the Global Leadership Initiative on Malnutrition (GLIM) criteria to identify patients with different degrees of malnutrition. Patients underwent a 3 to 4-week individual multidisciplinary rehabilitation program consisting of nutritional intervention (energy intake 27to30 kcal/die/kg and protein intake 1–1.3 g/die/kg), exercise for total body conditioning and progressive aerobic exercise with cycle- and arm-ergometer (45 min, 5 days/week). At admission and discharge from our Rehabilitation Unit, body composition and phase angle (PhA) (BIA101 Akern), muscle strength (handgrip, HG) and physical performance (Timed-Up-and-Go, TUG) were assessed. Results: At admission in all patients the mean weight loss, as compared to the habitual weight, was −12.1 (7.6)%, mean BMI was 25.9 (7.9) kg/m 2, mean Appendicular Skeletal Muscle Index (ASMI) was 6.6 (1.7) kg/m 2 for males and 5.4 (1.4) kg/m 2 for females, mean phase angle was 2.9 (0.9)°, mean muscle strength (HG) was 21.1 (7.8) kg for males and 16.4 (5.9) kg for females, mean TUG value was 23.7 (19.2) s. Based on GLIM criteria 29 patients (60% of the total) showed a malnutrition condition. 7 out of those 29 patients (24%) presented a mild/moderate grade and 22 patients (76%) a severe grade. After a rehabilitation program of an average duration of 25 days (range 13–46) ASMI increased, with statistically significant differences only in females ( p = 0.001) and HG improved only in males ( p = 0.0014). In all of the patients, body weight did not change, CRP/albumin ( p < 0.05) and TUG ( p < 0.001) were reduced and PhA increased ( p < 0.01). Conclusions: We diagnosed a malnutrition condition in 60% of our post SARS-Cov2 patients. An individualized nutritional intervention with adequate energy and protein intake combined with tailored aerobic and strengthening exercise improved nutritional and functional status. Highlights: Majority of Post-Covid-19 patients are malnourished based on GLIM criteria. Nutritional and exercise intervention improved outcome of Post-Covid-19 patients. Post-Covid-19 patients need nutritional surveillance or nutritional care plan.